FLIPPED CLASSROOM TEACHING IN HIGHER EDUCATION: AN ASSUMPTION OR AN INEVITABLE TOOL - Seereekissoon, Denisha Seedoyal (PEOPLE: International Journal of Social Sciences, 2018)
The conventional face-to-face lectures was effective decades ago in Higher Education. However, its efficacy is being questioned, nowadays, for the Generation Z and Millenials. The latter are technology-savvy and ‘always connected.’ It is becoming more and more challenging to retain students’ attention using traditional lectures as they are ‘known’ to be multi-tasking. Often, when one would be delivering a lecture, one can notice students getting bored, or diverted by their smartphones. This paper addresses a potential way of increasing students’ engagement in class by introducing Flipped classroom in Higher Education, particularly for the BA (Hons) Advertising, Public Relations and Media at the Middlesex University. Flipped classroom was chosen as recent studies (Steen-Utheim and Foldness, 2018; Gilboy et al, 2015; Pierce and Fox, 2002) had proved beneficial. A simple model of Action Research methodology (Dan, 1996), that consisted of planning, acting, observing and reflecting, was used. Video lectures were sent to students, for them to watch outside the classroom setting. During the actual face-to-face time, they were given practical exercises so that they had more hands-on experience. An observation of the practical session followed by a reflection on the feedback from the student lead to some critical findings. Most of them enjoyed the flipped classroom as they were able to watch the videos ‘several times’ and they learnt ‘innovatively’. Nevertheless, the major drawback was that there were some students who were not watching the video lectures at home. These led to future scope of research in the field.